2017
DOI: 10.1074/jbc.m116.771519
|View full text |Cite
|
Sign up to set email alerts
|

trans-Fatty acids promote proinflammatory signaling and cell death by stimulating the apoptosis signal-regulating kinase 1 (ASK1)-p38 pathway

Abstract: Food-borne -fatty acids (TFAs) are mainly produced as byproducts during food manufacture. Recent epidemiological studies have revealed that TFA consumption is a major risk factor for various disorders, including atherosclerosis. However, the underlying mechanisms in this disease etiology are largely unknown. Here we have shown that TFAs potentiate activation of apoptosis signal-regulating kinase 1 (ASK1) induced by extracellular ATP, a damage-associated molecular pattern leaked from injured cells. Major food-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 60 publications
(60 reference statements)
5
54
0
1
Order By: Relevance
“…30 In contrast, TFA promote pro-inflammatory signaling and cell death by stimulating the apoptosis signal-regulating kinase 1/p38 pathway. 31 In the present study, we demonstrated the relationship between circulating elaidic acid level and the incidence of TLR. Elaidic acid is a typical industrial TFA, produced by partial hydrogenation of vegetable oil.…”
Section: Discussionsupporting
confidence: 58%
“…30 In contrast, TFA promote pro-inflammatory signaling and cell death by stimulating the apoptosis signal-regulating kinase 1/p38 pathway. 31 In the present study, we demonstrated the relationship between circulating elaidic acid level and the incidence of TLR. Elaidic acid is a typical industrial TFA, produced by partial hydrogenation of vegetable oil.…”
Section: Discussionsupporting
confidence: 58%
“…Cells were lysed with the 1% Triton X-100 buffer [20 mM Tris-HCl (pH 7.4), 150 mM NaCl, 1% Triton-X100, 10% Glycerol, and 1% protease inhibitor cocktails (Nacalai Tesque, Kyoto, Japan)]. After centrifugation, the cell extracts were resolved by SDS-PAGE and analyzed as described previously (Hirata et al, 2017). The blots were developed with ECL (Merck Millipore, Burlington, VT, USA).…”
Section: Immunoblotmentioning
confidence: 99%
“…Guide RNAs (gRNAs) were designed to target a region in the exon 3 of p53 gene (5'-ATCTGAGCAGCGCTCATGGTGGG-3'), and the exon 4 of EGFR gene (5'-CTTTCTCAGCAA-CATGTCGATGG-3') using CRISPRdirect. gRNA-encoding oligonucleotide was cloned into lentiCRISPRv2 plasmid (addgene, Watertown, NY, USA), and knockout cells were established as previously described (Hirata et al, 2017). To determine the mutations of p53 and EGFR in cloned cells, genomic sequence around the target region was analyzed by PCR-direct sequencing using extracted DNA from each clone as a template and the following primers: 5'-AGAGACCCCAGTTGCAAACC-3'and 5'-CCCTGCCCTCAACAAGATGT-3' for p53, and primers: 5'-GGGCTAATTGCGGGACTCTT-3' and 5'-CCCAGTGCTGTAGAGCTGTC-3' for EGFR.…”
Section: Generation Of Knockout Cell Linesmentioning
confidence: 99%
“…3,4 Trans fatty acids affect the activities of macrophages, leading to an increase in pro-inammatory reactions and the occurrence of atherosclerosis. [5][6][7] Trans fatty acids can decrease the level of high-density lipoprotein cholesterol (HDL) and increase the level of low-density lipoprotein cholesterol (LDL), thereby increasing the risk of coronary heart disease. [8][9][10] It is well known that primary oxidation compounds or hydroperoxides can be formed in the oxidation of edible oils at high temperature or in the presence of metals, which can then be degraded to secondary oxidation compounds.…”
Section: Introductionmentioning
confidence: 99%